Acute and sub-acute toxicity of Pithecellobium dulce (Roxb.) Benth. stem bark hydroalcoholic extract on Wistar rats - Gérard A. Toudji; Kossivi Dosseh; Simplice D. Karou; Yao Adjrah; Kokou Anani; Yaovi Ameyapoh; Jacques Simpore (GarVal Editorial Ltda., 2017)
Context: Pithecellobium dulce (PD) is an annual herbaceous plant commonly used in African traditional medicine as a purgative, antipyretic, anti-ulcer and wound dressing agent. Aims: To evaluate the acute and sub-acute toxicity of P. dulce stem bark hydroethanolic extract in Wistar rats. Methods: In the acute test, a single dose of 5 g/kg body weight was administered to Wistar rats afterwards they were observed individually 4 hours post-dosing, and at least once daily for 14 consecutive days. The sub-acute toxicity was evaluated by daily oral administration of 0.5 and 1 g/kg extract, for 28 days. Biochemical and hematological parameters assessment as well as body and organ weights of the rats were carried out. Results: The limit dose of 5 g/kg did not cause any mortality or signs of acute toxicity on the rats during the experimentation period. In the sub-acute test, uterus-ovary-trompe (UOT) weight decreased dose-dependently: Control group (0.82 ± 0.03 g); Extract 0.5 g/kg (0.57 ± 0.06 g); Extract 1g/kg (0.48 ± 0.01 g) (p ˂ 0.01). Extract lowered urea values in female group treated with 1 g/kg (p < 0.01). Lymphocytes percentage was dose dependently increased in treated male groups: Control group (53.00 ± 0.58%); extract 0.5 g/kg (58.67 ± 0.67%) and extract 1 g/kg (60.67 ± 2.41%). Conclusions: These findings suggest that PD is relatively safe when administered orally in rats but is slightly atrophic for female reproductive organs.